Correction: A robust iron catalyst for the selective hydrogenation of substituted (iso)quinolones - Sahoo, Basudev (Chem Sci, 2018)
Correction for ‘A robust iron catalyst for the selective hydrogenation of substituted (iso)quinolones’ by Basudev Sahoo et al., Chem. Sci., 2018, DOI: ; 10.1039/c8sc02744g.